2002
DOI: 10.1093/jn/132.4.658
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens and Mycoestrogens Bind to the Rat Uterine Estrogen Receptor

Abstract: Consumption of phytoestrogens and mycoestrogens in food products or as dietary supplements is of interest because of both the potential beneficial and adverse effects of these compounds in estrogen-responsive target tissues. Although the hazards of exposure to potent estrogens such as diethylstilbestrol in developing male and female reproductive tracts are well characterized, less is known about the effects of weaker estrogens including phytoestrogens. With some exceptions, ligand binding to the estrogen recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 49 publications
3
102
1
2
Order By: Relevance
“…Four other laboratories, which either participated in phase 1 (Kanno et al 2001) or the coded single-dose studies in phase 2 (Kanno et al 2003), did Blair et al (2000) and Branham et al (2002). b The binding curves were generated in a single laboratory on the basis of a single protocol using closely interspersed concentrations and performed in triplicate.…”
Section: Results Of Phase 2 Dose-response Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Four other laboratories, which either participated in phase 1 (Kanno et al 2001) or the coded single-dose studies in phase 2 (Kanno et al 2003), did Blair et al (2000) and Branham et al (2002). b The binding curves were generated in a single laboratory on the basis of a single protocol using closely interspersed concentrations and performed in triplicate.…”
Section: Results Of Phase 2 Dose-response Studiesmentioning
confidence: 99%
“…These data are compliant with test substance selection recommendations to demonstrate the characteristics of a bioassay for validation studies and the relationship of a bioassay to other assays in a hierarchical, tiered approach (ICCVAM 1997;OECD 1998b). The chemical identities and estrogenreceptor binding data from Blair et al (2000) and Branham et al (2002) are shown in Table 1. The binding affinities of the selected weak agonists relative to 17β-estradiol cover a range of almost three orders of magnitude, for example, log -0.35 to -3.20, and even the two most potent selected agonists, GN and the metabolite of MX, are almost three orders of magnitude weaker than the reference EE agonist.…”
Section: Selection Of Weak Agonists and Dosesmentioning
confidence: 99%
“…There is evidence that phytoestrogens bind ERs and modulate a variety of estrogen-dependent processes (35,36). It is also possible that diets with higher phytoestrogen levels exert their estrogenic activity by regulating ER␣ and PR expression, which then affects uterine responsiveness to estrogen and P 4 .…”
Section: Commercial Diets Alter Estrogen-responsive Gene Expression Imentioning
confidence: 99%
“…Phytoestrogens can induce biologic responses due to their structural similarity to 17β-estradiol when they are consumed in the diet [16]. The biologic responses from phytoestrogens include estrogenic, anti-estrogenic, anti-oxidative, anti-viral, anti-bacterial, and antiproliferative effects [11].…”
Section: Introductionmentioning
confidence: 99%